Stimulus dependent diversity and stereotypy in the output of an olfactory functional unit - Ezequiel M. Arneodo (Nature Portfolio, 2018)
Mitral/tufted (MT) cells connect to a single glomerulus and receive inputs from sensory neurons expressing the same odorant receptor. Here the authors report that sister MT cells connected to the M72 glomerulus exhibit variable responses to most M72 ligands but respond in a reproducible and stereotyped way to a high-affinity M72 ligand.